A produção de violência simbólica e a patologização como instrumento pedagógico - Barbi, Kathy Briones [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Formal education plays a fundamental role in the development of children and adolescents within society. However, in recent times, there has been a persistent concern regarding school failure and the involvement of a “palette” of behaviors considered inappropriate for the educational environment, which intersect within this issue. This discussion, grounded in the school environment, has proven to be pertinent, and this dynamic has raised questions about the potential symbolic violence embedded in the process of referring students to educational psychology and institutional psychopedagogy services in response to behavioral and learning difficulties—most notably those related to reading and writing skills, which are expected by the end of the first cycle and in Portuguese language subjects in the second cycle. The objective of this research is to reflect on how the individualizing and pathological perspective of resolving and adapting to these deficits could be understood as a form of symbolic violence. Using a qualitative and theoretical-methodological approach, the study employed focus groups with teachers of 4th and 5th grades in elementary education (Cycle I) and Portuguese language teachers, as well as semi-structured interviews with institutional psychopedagogists and the Technical-Pedagogical Support Team responsible for the training of 4th and 5th-grade teachers and cycle recovery programs in the municipal education network of Araras-SP. Data analysis was conducted based on Pierre Bourdieu's theoretical framework, particularly the conceptual perspective of symbolic violence. The aim of these discussions and contributions is to understand how the basic education network in this municipality has been influenced by the pathologization of school failure.

A educação formal possui papel fundamental no que concerne ao desenvolvimento de crianças e adolescentes dentro da sociedade. Contudo, tem-se observado nos últimos tempos, uma preocupação persistente em relação ao fracasso escolar e o envolvimento de uma “paleta” de comportamentos considerados inadequados ao ambiente educacional, os quais se contracenam dentro dessa problemática. Essa discussão no chão da escola, tem se revelado pertinente, e tal movimento, tem levantado questões de uma possível violência simbólica contida no processo de encaminhamentos aos setores de psicologia educacional e psicopedagogia institucional frente às dificuldades comportamentais e de aprendizagem, mais pontualmente, referentes as inaptidões de leitura e escrita, habilidades tais, esperadas para o final do ciclo I e para disciplinas de Língua Portuguesa no ciclo II. O objetivo dessa pesquisa é refletir o quanto a visão individualizante e patológica da resolução e adequação desses déficits, poderia ser compreendida como uma forma de violência simbólica. Dentro de uma abordagem qualitativa, Teórico-metodológica, utilizou-se de grupo focal com a participação de professores de 4º.s e 5º.s anos do ensino fundamental I e de língua portuguesa, entrevistas semiestruturadas com os psicopedagogos institucionais e com a equipe de Apoio Técnico Pedagógico responsáveis pela formação dos professores de 4º.s e 5º.s anos e da recuperação de ciclo, na rede municipal de ensino de Araras-SP. A análise dos dados da pesquisa foi feita a partir do referencial teórico de Pierre Bourdieu na perspectiva conceitual da violência simbólica, onde essas discussões e contribuições, objetiva compreender como a rede básica de ensino deste município tem sido atravessada pela patologização do fracasso escolar.
The production of symbolic violence and pathologization as a pedagogical instrument
Keywords: Violência simbólica; Medicalização da educação; Patologização do ensino; Fracasso escolar; Educação básica; Symbolic violence; Medicalization of education; Pathologization of teaching; School failure; Basic education